Daily Behavior of Bangla Tigers (Panthera tigris tigris) in Ex-situ Conservation Site, Serulingmas Zoo, Banjarnegara - Aswi Andriasari Rofiqoh; Siti Rukayah; Erie Kolya Nasution; Ridha Nabila Priyani (Universitas Nasional Jakarta, 2022)
Panthera tigris tigris is a subspecies of Panthera tigris, which originates from India and has been declared an endangered species. Bengal Tigers are facing a severe decline in their habitat and population. Ex-situ conservation of Panthera tigris tigris has been done in some Indonesian zoos to enhance its population. Serulingmas Zoo is one of the ex-situ conservation sites. This study aims to observe the tigers’ daily behavior in captivity as a conservational database. Behaviors of Bangla tigers (Panthera tigris tigris) in captivity were investigated from February to March 2021 in Serulingmas Zoo, Banjarnegara. Instantaneous Focal animal sampling has been conducted to observe the seven tigers. The results showed that the behavior could be divided into Moving, feeding, resting, social and other behaviors (including drinking, urinating, grooming, stretching, and defecating). The daily behavioral patterns showed resting behaviors as the most significant (33.56 %). The pacing activity (24.43%) counted as a frequent one that showed the tigers had altered their natural behavior. The eating and social 16.42%, and 13.03%), respectively. Defecating was reported as a minor activity (0.22%). Generally, the daily behaviors of Bangla tigers captivated at Serulingmas zoo showed the alteration in behavior patterns.